2018
DOI: 10.1177/1475921718764848
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter beamforming and weighted image fusion–based multiple signal classification algorithm for corrosion monitoring

Abstract: With the increase in aging aircrafts, corrosion monitoring has attracted much attention in the structural health monitoring area. Multiple signal classification has been gradually applied to structural health monitoring area as a new promising method because of its ability of directional scanning and the potential to monitor multiple signal sources. However, applying multiple signal classification algorithm to monitor real damage still faces some challenges. First, the scattered Lamb waves obtained using a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Qing et al [40] proposed a damage monitoring method for torsional elastic waves, which realized the monitoring of high attenuation honeycomb structures. Bao et al [41,42] proposed the transmitter beamforming MUSIC algorithm based on a bilinear array and achieved low SNRs corrosion damage monitoring in a reinforced aviation structure. The array error was also corrected, and thus, the localization accuracy of the algorithm was improved.…”
Section: Introductionmentioning
confidence: 99%
“…Qing et al [40] proposed a damage monitoring method for torsional elastic waves, which realized the monitoring of high attenuation honeycomb structures. Bao et al [41,42] proposed the transmitter beamforming MUSIC algorithm based on a bilinear array and achieved low SNRs corrosion damage monitoring in a reinforced aviation structure. The array error was also corrected, and thus, the localization accuracy of the algorithm was improved.…”
Section: Introductionmentioning
confidence: 99%
“…In the existing SHM technologies, the damage imaging method which has high signal-to-noise ratio can visually indicate damage location and size. Examples of these imaging techniques include the delay-and-sum method [6][7][8][9], time reversal method [10][11][12][13], probabilistic diagnostic algorithm [14][15][16][17], phased array method [18][19][20][21], multisignal classification method [22][23][24][25][26], and spatial-wavenumber filter method [27][28][29][30][31][32][33][34][35]. Among them, the spatial-wavenumber filter method, which has been extensively studied, can extract the specific mode of the Lamb wave, distinguish the incident wave and damage scattering wave, and reduce the overlap of Lamb wave signals [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Lamb wave-based structural health monitoring (SHM) technique has been proved to be one of the strongest techniques for online and real-time damage detection of aircraft structures because of the superior capability of travelling long distances and covering large monitoring area with limited numbers of piezoelectric sensors [1]. Plenty of Lamb wave-based damage detection algorithms, including delay and sum [2,3], phased array [4,5], tomography [6,7,8,9,10,11], and migration [12,13], have been developed. Comprehensive reviews on the application of Lamb wave for structural health monitoring can be found in the literature [1,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews on the application of Lamb wave for structural health monitoring can be found in the literature [1,14,15]. Depending on whether reference data of Lamb wave in the pristine structure is needed or not, these algorithms can be divided into two categories, i.e., reference-free algorithms [16,17,18,19] and reference-dependent ones [2,3,4,5,6,7,8,9,10,11,12,13]. Reference-dependent algorithms are more practical than reference-free ones for real application in aircraft structures due to the complex nature of the Lamb wave, including multiple mode, modes conversion and scattering at the boundary.…”
Section: Introductionmentioning
confidence: 99%